Evidence against T-cell immunoglobulin from radioimmunoassay on serum and cells from bursectomized chickens. - Jensenius, J C (1976)
A radioimmunoassay with a sensitivity of about 50 pg of chicken immunoglobulin (Ig) was developed and employed for the estimation of Ig in the serum and in extracts of cells from hormonally bursectomized chickens. Chickens, which were judged agammaglobulinaemic by rocket immunoelectrophoresis, had at 12 weeks of age 5-100 ng of Ig/ml of serum. The Ig concentration was decreasing with a half life of 5 days. Thymus and spleen cells from such hypogammaglobulinaemic chickens were extracted with non-ionic detergents, acid urea, or combinations of urea and detergent, and the extracts were analysed for Ig by the inhibition assay. The amount of Ig found in extracts from thymocytes corresponded to less than a hundred molecules of 7S Ig/cell with a lower value of less than five molecules/cell, while extracts of spleen cells contained Ig corresponding to 60-300 molecules of Ig/cell. The inclusion in the media of a number of protease inhibitors did not increase the recovery. Extracts of thymus and spleen cells from untreated chickens contained Ig corresponding to 10-20 X 10(3) and 50-150 X 10(3) molecules of Ig/cell respectively. The results demonstrate the profound hypogammaglobulinaemia of bursectomized chickens and question the concept of an active production of receptor Ig by bursa-independent T cells.